Infinite Fibonacci Series Arising from Generalized Second Order - Difference Equations - Britto Antony Xavier, G.; Mohan, B.; G. Gerly, T.; Suganya, R. (International Journal of Engineering and Technology, 2018)
In this paper, we extend finite Second order -Fibonacci formula to infinite Second order -Fibonacci formula and also obtain the sum of infinite Second order -Fibonacci multi-series formula. Suitable examples are inserted to illustrate our findings.Â